Genome−wide identification and analysis of LEA_2 gene family in alfalfa (Medicago sativa L.) under aluminum stress - Zhang, Yujing; Fan, Nana; Wen, Wuwu; Liu, Siyan; Mo, Xin; An, Yuan; Zhou, Peng (Frontiers in Plant Science, 2022)
Late embryonic development abundant proteins (LEAs) are a large family of proteins commonly existing in plants. LEA_2 is the largest subfamily in the LEA, it plays an important role in plant resistance to abiotic stress. In order to explore the characteristics of LEA_2 gene family members in alfalfa (Medicago sativa L.), 155 members of LEA_2 (MsLEA_2) family were identified from alfalfa genome. Bioinformatics analysis was conducted from the aspects of phylogenetic relationship, chromosome distribution, chromosome colinearity, physical and chemical properties, motif composition, exon-intron structure, cis-element and so on. Expression profiles of MsLEA_2 gene were obtained based on Real-time fluorescent quantitative PCR (qRT-PCR) analysis and previous RNA-seq data under aluminum (Al) stress. Bioinformatics results were shown that the MsLEA_2 genes are distributed on all 32 chromosomes. Among them, 85 genes were present in the gene clusters, accounting for 54.83%, and chromosome Chr7.3 carries the largest number of MsLEA_2 (19 LEA_2 genes on Chr7.3). Chr7.3 has a unique structure of MsLEA_2 distribution, which reveals a possible special role of Chr7.3 in ensuring the function of MsLEA_2. Transcriptional structure analysis revealed that the number of exons in each gene varies from 1 to 3, and introns varies from 0 to 2. Cis-element analysis identified that the promoter region of MsLEA_2 is rich in ABRE, MBS, LTR, and MeJARE, indicating MsLEA_2 has stress resistance potential under abiotic stress. RNA-seq data and qRT-PCR analyses showed that most of the MsLEA_2 members were up-regulated when alfalfa exposed to Al stress. This study revealed that phylogenetic relationship and possible function of LEA_ 2 gene in alfalfa, which were helpful for the functional analysis of LEA_ 2 proteins in the future and provided a new theoretical basis for improving Al tolerance of alfalfa.